Latency analysis of WirelessHART control message with variable payload - Chung, T.D. (Institute of Electrical and Electronics Engineers Inc., 2017)
Since 2007, the emerging wireless technologies for industrial applications such as wireless highway addressable remote transducer (WirelessHART), and ISA100.11a have been used mainly for process monitoring application only. When gearing toward control application of these technologies a common factor that often being considered is network latency or known as delay. Although the typical network round trip (upstream, and downstream) delays have been reported in recent researches, only few have discussed on the relationship between message payload length and the network induced delays. Therefore, this paper carries out an investigation into the effect of variable payload on the delay of control message sending from controller to plant actuator using the widely preferred industrial wireless technology, WirelessHART. © 2016 IEEE.